Economic Development through Electronic Commerce: Case Study - Arshi Naim (Web of Journals Publishing, 2023)
- Electronic Commerce (Ecom) is now adopted by all the firms especially during the Covid 19 pandemic. Ecom is the process of buying and selling of products and services in an online environment with the help of telecommunicating devices. This research attempts to measure the role of Ecom in economic activity and in trade and tariff revenue collection. The share of value added that potentially lends itself to electronic trade represents around 45 percent of GDP, most importantly distribution, finance and business services.  Ecom is also likely to increase sales in many services sectors drastically. Regardless of the growing importance of Ecom for economic activity and trade, tariff revenue loss from Ecom is likely to be minimal. The revenue collected on these products amounts to less than one percent of total tariff revenue in most countries.  Even if some of this trade moved “online”, tariff revenue loss would be only a very small share of tariff revenue.
Keywords: Ecommerce, International Trade, Services Trade, Tariffs, Tariff Revenue, Technological Change